Organizational leverage effect in innovation - DE MEYER, Arnoud Cyriel Leo (Institutional Knowledge at Singapore Management University, 1991)
An innovation cannot act in a vacuum, but should enlist the help of ‘partners in innovation’ in order to improve the productivity of the innovation process. In this paper, Arnoud De Meyer uses a number of case studies to show how this leverage of the innovation process can be used under different circumstances, and how the leveraging process can be organized.